ANALISIS PENGARUH PENAMBAHAN ABU CANGKANG KELAPA SAWIT TERHADAP STABILITAS DAN KEPADATAN ASPA MODIFIKASI PG 76 (AC-BC) - Rosyad, Farlin; Yudanto, Galuh (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Roads are infrastructure that plays a very important role in the progress of a region, which is a link between one region and other regions.. In an effort to add substitutes for fine materials that can be used as ingredients in asphalt mixtures, palm shell ash, which is easily obtained, was used in research as an alternative fine material in asphalt mixtures. The asphalt used in this research is PG 76 modified asphalt originating from PT. Perdana Eternal Mighty. This research was carried out with the aim of finding out the value of a mixture of palm shell ash as a fine fraction material for AC-BC layers in terms of stability and density. The percentage of palm shell ash content used in this research was 0%, 4%, 6% and 8%. This research uses the Marshall Test method by reviewing the effect of palm oil shell ash on stability and density values. The highest value of stability is the percentage of palm shell ash of 8% with a value of 1342 Kg and the highest value of density is the percentage of palm shell ash of 8% with a value of 2.301 gr/cc.Keywords: Palm shell ash, PG76 modified asphalt, AC-BC, Stability, Density